DAMPAK DESENTRALISASI FISKAL TERHADAP KESEJAHTERAAN EKONOMI DAN KEADILAN SOSIAL DI PROVINSI KEPULAUAN RIAU - Yunanda, Sutia (JURNAL AKUNTANSI BARELANG, 2025)
This study aims to analyze the impact of fiscal decentralization on economic welfare and social justice in the Riau Islands Province. Fiscal decentralization, which includes economic growth, distribution of General Allocation Funds and Special Allocation Funds , is expected to increase regional autonomy in budget management so that it can accelerate local economic development and improve the quality of life of the community. In the context of the Riau Islands Province, which consists of remote islands with significant geographical challenges, the implementation of fiscal decentralization occurs in the problem of inter-regional inequality, limited access, and high distribution costs of funds. This study uses a qualitative analysis method to measure the fiscal impact on economic growth, equitable development, and increasing the Human Development Index in several districts/cities in the Riau Islands. The results of the study show that fiscal decentralization contributes to improving economic welfare in developed areas such as Batam and Tanjungpinang. However, inequality in welfare and access to basic services still occurs in remote areas such as Lingga and the Anambas Islands. The limited capacity of local governments in budget planning and supervision also hinders the optimal use of General Allocation Funds and Special Allocation Funds throughout the region. Overall, fiscal decentralization has a positive impact on economic growth and public welfare in the Riau Islands Province, but there are still challenges in realizing equitable social justice. Therefore, a more adaptive and collaborative strategy is needed between the central and regional governments to overcome geographical barriers, increase administrative capacity, and ensure equitable distribution of benefits from fiscal policies throughout the Riau Islands.